IMPLEMENTASI KEBIJAKAN DISKRESI PADA SISTEM PELAYANAN PUBLIK DI KOTA TEGAL - Ikmal Jaya (UNISSULA, 2014)
Bureaucratic discretion in local government as one of the efforts the effectiveness of public services in Tegal city publication in urgent circumstances is a condition that arises suddenly public interest that must be resolved quickly, which to resolve the issue, the legislation has not been set. The approach used in this study is a socio-juridical approach, the method or procedure used to solve research problems by examining secondary data such as material laws or regulations applicable law followed by conducting research on primary data in the field. The results obtained that 1) Discretion Policy Implementation bureaucracy in local government as one of the efforts the effectiveness of public services in Tegal publication in urgent circumstances is a condition that arises suddenly public interest that must be resolved quickly, which to resolve the issue the legislation has not been set or just set in general and the situation should not be created due to error or action by the Board of Administration officials who perform discretionary, 2) Constraints in the discretion of the bureaucracy in local government as one of the efforts of service effectiveness public in Tegal is insufficient fee due to excessive demand of bureaucratic discretion program.